Gender Perspective in Understanding Islamic Law on Polygamy: A Critical Analysis of Classical and Contemporary Fiqh Teachings - Syafi’i; Siti Ropiah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the understanding of Islamic law regarding polygamy from a gender perspective, focusing on the comparison between classical jurisprudence (fiqh) teachings and contemporary interpretations. Polygamy is a complex issue in Islamic law, often sparking debates about gender justice, women's rights, and its relevance in modern social contexts.The research employs a qualitative approach with a critical analysis of classical fiqh texts and contemporary scholars' views. The findings reveal that classical fiqh teachings tend to position women in subordinate roles, emphasizing obedience to husbands. However, contemporary perspectives influenced by gender equality principles and maqasid al-shariah offer new insights that prioritize justice and the protection of women's rights.The study concludes that a gender-based approach can provide more relevant and equitable interpretations of Islamic law on polygamy for modern societies. It also identifies challenges in integrating gender equality principles into Islamic legal understanding, particularly amidst cultural resistance and conservative interpretations.